The role of brand experience on brand equity: Mediating effect of authenticity in new luxury fashion brands - Sally Mohamed Amer; Amany Ahmed Elshimy; Moataz El Sayed Mohamed Abo El Ezz (Cogent Business & Management, 2023)
The role of new luxury fashion brand experience and authenticity on brand equity has not been sufficiently explored empirically. The current study offers a model of the relationship between brand experience, brand authenticity, and brand equity, considering the rising relevance of new luxury fashion brand authenticity and its advantages for practitioners. We used a self-administrative questionnaire, and the number of participants was 411 customers of new luxury fashion brands. Partial-least squares structural equation modeling (SmartPLS software, version 4) is used to evaluate the proposed model. The findings indicate that, with the exception of affective experience, all brand experience dimensions have a direct and indirect impact on brand equity dimensions, considering that brand authenticity is a fully mediating factor. The research results provide valuable advice to help brand managers engage more in practices that enhance brand equity by building memorable and pleasant brand experiences, leading to improved brand authenticity.
Keywords: 650; attribution theory; brand authenticity; brand equity; brand experience; new luxury fashion brands